Effects of physical exercise on improving erectile function: a systematic review and meta-analysis of randomized controlled trials - Jingxian Chai; Qiuhua Zhang; Xue Li; Wenjun Wang; Chunjing Tu; Huiming Huang (Journal of Men's Health)
Background: The study aims to determine the effects of physical exercise (PE) on improving erectile function in adult men with erectile dysfunction (ED) and to explore appropriate clinical exercise regimens through subgroup analyses of factors such as exercise intensity and cycles. Methods: We conducted a systematic review of articles describing randomized controlled trials (RCTs), and conducted subgroup analyses based on demographic and exercise program characteristics. The primary outcome indicator was the International Index of Erectile Function (IIEF) score, which was meta-analyzed to determine the combined effect size. Qualitative analysis was conducted on other relevant indicators. Results: A total of 10 studies were included in the meta-analysis and 6 in the qualitative analysis. The results of the meta-analysis indicated a standardized mean difference (SMD) of 0.892 with a 95% confidence interval of [0.395–1.388], a Hedges’ g of 0.247, and an I2 of 88.6% (p < 0.01). Subgroup analysis showed that the SMD effect was greater in the <60 years age group, the 0–3 months exercise cycle and the low-intensity group, with p < 0.05; no significant differences were observed in the subgroups according to country, object or intervention exercise frequency. Conclusions: This study demonstrated that PE significantly reduces IIEF scores in patients with ED compared with other interventions for the treatment of ED, especially in ED patients under 60 years of age with chronic disease state (CDS). Low-intensity with a 0–3 months duration was more effective in improving erectile function. This effect is not related to the country, exercise frequency or intervention group with or without combined drug intervention. These findings have practical value in guiding healthcare professionals in the selection of selecting clinical exercise prescription programs. In addition, physical exercise is also beneficial in improving body mass index, blood pressure and blood sugar. The PROSPERO Registration: CRD42023445949, http://www.crd.york.ac.uk/PROSPERO.